Fashion designing simulating environmental art (the southern region) as one of the Small Enterprises to stimulate tourism according to the vision of 2030 for the Kingdom of Saudi Arabia - Elkherbawy, Randa Monier (Journal of Humanities & Social Sciences, 2023)
The research dealt with the environmental and cultural diversity found in the southern region and the rich heritage of life... and the extent of exploiting this region to raise the level of the state's economy and develop it. The research problem came in how to support the treatment of the problem of unemploymentAnd the extent of the possibility of promoting tourism through a variety of fashion designs. The aim of the research is to develop environmental art for the southern region through fashion designs from the heritage of the southern region to contribute to revitalizing tourism and directing youth to small projects. The research followed the analytical descriptive approach through the analytical study of environmental and heritage art of the southern region and the experimental approach of Through innovative designs drawn through programs (sketchbook, illustrator), designs implemented on the ground, and technical studies of environmental, heritage and tourism art.The spatial search boundaries were limited to the southern region (Asir, Jazan, Najran, and Al-Baha) as it is one of the most diverse regions in terms of geographical nature, topography, and temporal boundaries, for three months, from March to the end of May 2022. The results came with strong acceptance of the designs implemented from the questionnaire presented to consumers. The research recommended the necessity of paying attention to environmental art, preserving the culture of the geographical area over time, and supporting small projects, which in turn contribute to increasing the economic growth of the state.
Keywords: fashion design; environmental art; tourism; Vision 2030 for the Kingdom of Saudi Arabia